2004
DOI: 10.1023/b:nere.0000013735.50736.0a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DHEA Glutamate Release from Synaptosomes of Rats at Different Ages

Abstract: Dehydroepiandrosterone (DHEA) exerts multiple effects in the central nervous system. Most of them seem to be mediated through their nongenomic actions on neurotransmitter receptors, and these actions occur within seconds or milliseconds. DHEA increases neuronal excitability, enhances neuronal plasticity, and has neuroprotective properties. By investigating glutamate release from synaptosomes of rats at different ages (from 17 days to 12 months), we observed that (i) there is an increase in basal and K(+)-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…41 However, we also found that extracellular Ca 2þ , but not NMDA receptor or sigma-1 receptor activation, is crucial for presynaptic facilitation of glutamate release by DHEAS. Although our findings were not compatible with those of previous studies, 12,17,40 DHEAS is also known to activate the Ca 2þ -activated K channel (KCa) 42 and Ca 2þ -permeable ion channels, such as P2X purinergic receptors, 5,43 which may account for these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…41 However, we also found that extracellular Ca 2þ , but not NMDA receptor or sigma-1 receptor activation, is crucial for presynaptic facilitation of glutamate release by DHEAS. Although our findings were not compatible with those of previous studies, 12,17,40 DHEAS is also known to activate the Ca 2þ -activated K channel (KCa) 42 and Ca 2þ -permeable ion channels, such as P2X purinergic receptors, 5,43 which may account for these discrepancies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results suggest that DHEAS predominantly enhances nociceptive synaptic transmission at presynaptic sites. Previous studies have shown that DHEAS increased glutamate release from presynaptic terminals 12,40 and potentiated excitatory synaptic transmission 17 via sigma-1 receptor activation. Moreover, presynaptic NMDA receptor activation is thought to be associated with the pathophysiology of neuropathic pain.…”
Section: Discussionmentioning
confidence: 93%
“…The results obtained are in agreement with previous studies that show a protective effect of DHEA on oxidative stress, apoptosis and alteration in mitochondrial electron transport induced in different experimental models [12,[22][23][24] . In this line, Aragno's group [12] found that DHEA orally at 4 mg/day for 21 days protected against oxidative stress induced by hyperglycemia in rat synaptosomes.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, in vivo DHEA administration was tested for its tentative neuroprotection and antioxidative role. Lhullier et al (2004) demonstrated that in vitro effect of DHEA on synaptosomal glutamate release depends on the age of rats, it decreases the basal glutamate release from synaptosomes of old rats (12 months), with no effect on young rats (17 days). DHEA and DHEAS (100 nm) can prevent/reduce the neurotoxicity of NMDA, both in vitro and in vivo models (Kimonides et al 1998).…”
Section: Discussionmentioning
confidence: 98%